Comparative toxicity assessment of glyphosate and two commercial formulations in the planarian Dugesia japonica - Fuselier, S. Grace; Ireland, Danielle; Fu, Nicholas; Rabeler, Christina; Collins, Eva-Maria S. (Frontiers in Toxicology, 2023)
Glyphosate is a widely used, non-selective herbicide. Glyphosate and glyphosate-based herbicides (GBHs) are considered safe for non-target organisms and environmentally benign at allowed usage concentrations. However, their increased use in recent years has triggered questions about possible adverse outcomes due to low dose chronic exposure in animals and humans. While the toxicity of GBHs has primarily been attributed to glyphosate, other largely unstudied components of GBHs may be inherently toxic or could act synergistically with glyphosate. Thus, comparative studies of glyphosate and GBHs are needed to parse out their respective toxicity. We performed such a comparative screen using pure glyphosate and two popular GBHs at the same glyphosate acid equivalent concentrations in the freshwater planarian Dugesia japonica. This planarian has been shown to be a useful model for both ecotoxicology and neurotoxicity/developmental neurotoxicity studies. Effects on morphology and various behavioral readouts were obtained using an automated screening platform, with assessments on day 7 and day 12 of exposure. Adult and regenerating planarians were screened to allow for detection of developmentally selective effects. Both GBHs were more toxic than pure glyphosate. While pure glyphosate induced lethality at 1 mM and no other effects, both GBHs induced lethality at 316 µM and sublethal behavioral effects starting at 31.6 µM in adult planarians.